2021
DOI: 10.1088/1361-665x/ac2811
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of 3D printed re-entrant chiral auxetic (RCA) geometries under in-plane and out-of-plane loadings

Abstract: Three-dimensional printing of auxetic materials is an emerging research field due to their intriguing negative Poisson's ratio (NPR) behaviour which enables improved load resistance than conventional materials for various applications. In this research, re-entrant chiral auxetic (RCA) structures of three different geometries were printed using polylactic acid (PLA) filament. The PLA material was also characterised in compression and tension. In total, 27 RCA specimens of varied cell sizes were designed, printe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…According to the literature consulted, studies have been found that evaluate mechanical properties in 3D printed auxetic materials, which have geometrical and structural characteristics belonging to the group of mesh structures, i.e., structures composed of elements joined without linkage. The literature reports the maximum tensile stress of 1.5 MPa using PLA printed chiral auxetic geometries of various sizes, obtaining strains in the range from 1.5% to 7.5%; however, this higher strain of 7.5% is obtained by reducing the stress, since the maximum stress of 0.58 MPa was obtained for this type of structure [ 26 ]. Another study in auxetic materials reports tensile stresses of 1.6 to 2.7 MPa with strains in the range from 0.5% to 9.2% [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature consulted, studies have been found that evaluate mechanical properties in 3D printed auxetic materials, which have geometrical and structural characteristics belonging to the group of mesh structures, i.e., structures composed of elements joined without linkage. The literature reports the maximum tensile stress of 1.5 MPa using PLA printed chiral auxetic geometries of various sizes, obtaining strains in the range from 1.5% to 7.5%; however, this higher strain of 7.5% is obtained by reducing the stress, since the maximum stress of 0.58 MPa was obtained for this type of structure [ 26 ]. Another study in auxetic materials reports tensile stresses of 1.6 to 2.7 MPa with strains in the range from 0.5% to 9.2% [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Small-scale samples were 3D printed and tested under compression and tension to ascertain their strength and deformation characteristics. The re-entrant chiral cell size has been shown to affect the mechanical properties of the re-entrant chiral auxetics [ 26 ]. Similarly, several geometries of re-entrant chiral auxetic (RCA) structures created using 3D printing have been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the re-entrant structure of auxetic materials results in NPR due to which these materials contract in all directions while compressed or stretched in all directions when extension is applied along one of their axes. These re-entrant auxetic topologies can be developed through thermo-mechanical, braiding, injection moulding and additive manufacturing methods, which is why the auxetic materials are also termed as auxetic metamaterials [5]. These auxetic metamaterials have been found suitable to develop composites of enhanced mechanical resistance for stress resistance, vibration damping and shock energy absorption [6].…”
Section: Introductionmentioning
confidence: 99%
“…Auxetic materials are known for their exceptional deformation behavior under external forces, demonstrating a transverse enlargement or contraction when stretched or compressed longitudinally. Since the report of auxetic foams in 1987, 1 auxetic materials have experienced tremendous development, covering a series of materials such as fibers, [2][3][4] yarns, [5][6][7] knitted fabrics, [8][9][10] woven fabrics, [11][12][13] composites, [14][15][16][17] and metamaterials, [18][19][20][21] etc. Due to the unique deformation behavior and energy absorption ability, auxetic materials have demonstrated great potential applications in perfect-fitting clothing, protective equipment, high-performance footwear, high-sensitivity transducers, soft robots, wearable devices, and even aircraft components, etc.…”
Section: Introductionmentioning
confidence: 99%